Determination of Automobile Road Section Capacity with Due Account of Weather and Environmental Conditions of the Republic of Belarus - Yu. A. Bogdanovich (Наука и техника)
The paper considers a number of factors that influence on automobile road section capacity. It is proved that it is necessary to take into account weather and environmental conditions in the methodology for road capacity evaluation. It is proposed to determine the road capacity for the most difficult period of a year from the point of view of traffic and roadway conditions. This period of a year is considered as a reference one which is used for road capacity evaluation in the given climatic zone.